Occurrence of Mycobacterium avium subsp. paratuberculosis in road killed wild carnivores in Portugal - Matos, Ana Cristina (2013)
Occurrence of Mycobacterium avium subsp. paratuberculosis in road killed wild carnivores in Portugal.